Jean-Christophe Le Coze and the study of socio technological risks - Hurtado, Sandra Lorena Beltran; Simões, Raoni Rocha; de Almeida, Ildeberto Muniz [UNESP]; Vilela, Rodolfo Andrade de Gouveia; Le Coze, Jean-Christophe (My University, 2025)
Jean-Christophe Le Coze has been working for the INERIS National Institute for Industrial Environment and Risks in France for more than 20 years now. He started his career as a safety engineer, but very quickly moved into the human and social sciences. From the beginning of his career, he was brought in with the idea that engineers could incorporate Human Factors in their visions and practices of safety. He then spent almost a year at the Technical University of Delft in the Safety Science Group. After that there was an accident in a French pyrotechnic plant in 2003, and Jean-Christophe Le Coze, in charge of the investigation, wrote a report showing the importance of the Human and Organisational Factors behind this event. It was a moment in France during which high-hazardous plants were questioned and were at the heart of the political agenda in terms of developing adequate regulation. Since then, he has contributed significantly to the advancement of knowledge in the safety area. One of his publications “Thirty years of accidents: the new face of socio-technological risks” was translated into Portuguese and published in 2023. This interview highlights the main concepts of the book and current challenges for accident prevention.
Jean-Christophe Le Coze e o estudo dos riscos sociotecnológicos
Keywords: Accident Prevention; Occupational Health; Safety; Socio Technological Risks